Analysis of the wind regime at high spatial-temporal resolution in the itacaiúnas river watershed, eastern amazon - Tavares, Alexandra Lima; Da Silva, Renato Oliveira; Do Carmo, Alexandre Melo Casseb; Martins, Gabriel Caixeta; Nascimento, Wilson Da Rocha; Ferreira, Douglas Batista Da Silva; Da Silva, Marcio Sousa; Costa, Carlos Eduardo Aguiar De Souza; Pontes, Paulo Rógenes; Tedeschi, Renata Gonçalves (Frontiers in Earth Science, 2023)
In the present study, hourly wind direction and speed data from six subregions along the Itacaiúnas River watershed (IRW) are analyzed over a one-year period. The data are acquired from six hydrometeorological stations located in areas of the IRW with different characteristics of land use and plant cover. Among the stations studied, Serra Leste (mine/pasture) stands out, with prevailing winds from the southeast and the east-southeast, in addition to higher wind speeds. In contrast, at the Salobo (forest) station, the lowest wind speeds are observed, and this station presents the highest percentage of calm (60%) in the series. In the analysis of the daytime (from 6 am to 5 pm) and nighttime (from 6 pm to 5 am) wind cycles, the breeze and mesoscale circulation system is identified. Predominantly northerly winds are observed acting on the Abadia Farm and IFPA (Federal Institute of Education, Science and Technology of Pará) Rural stations, both during the day and at night, overlapping with the local breeze effects. Daily (24 h) and associated breeze circulation (12 h) cycle frequency signals are identified through wavelet transform analyses of the wind for all stations. The interference from large-scale phenomena, such as the Intertropical Convergence Zone (ITCZ) and the South Atlantic Convergence Zone (SACZ), which operate in the region, is evident; this objectively suggests that these systems modulate small-scale rainfall. Finally, the data show that the differences in wind patterns are also due to environmental aspects such as plant cover, land use, and topography.